2013
DOI: 10.1002/chem.201204188
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Material Properties in Fluorescence Anion Sensor Arrays: A General Approach

Abstract: As the demand for probes suitable for sensor development increases, investigation of approaches that utilize known successful receptors gains in general importance. This study describes a two-prong approach that can be used as a guide to developing sensors from known receptors. First, the conversion of a simple receptor, calix[4]pyrrole, into a fluorescent probe to establish a ratiometric signal is described. Secondly, the sensors that employ an output from a single ratiometric calix[4]pyrrole probe are fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 99 publications
(64 reference statements)
0
43
0
Order By: Relevance
“…Anzenbacher et al developed a fluorescent probe molecule based on an octamethylcalix[4]pyrrole structure that is capable of anion binding while displaying an anion-specific change in fluorescence. 47 Doping into poly(ether-urethane) matrices leads to ion-selective optodes operating with a co-extraction mechanism. Neves, Lodeiro and coworkers synthesized new corrole derivatives that showed sensing ability towards the spherical halide ions F À , Cl À , Br À , and I À , the linear anion CN À and the bulky anions CH 3 COO À and H 2 PO 4 À .…”
Section: Photoluminescencementioning
confidence: 99%
“…Anzenbacher et al developed a fluorescent probe molecule based on an octamethylcalix[4]pyrrole structure that is capable of anion binding while displaying an anion-specific change in fluorescence. 47 Doping into poly(ether-urethane) matrices leads to ion-selective optodes operating with a co-extraction mechanism. Neves, Lodeiro and coworkers synthesized new corrole derivatives that showed sensing ability towards the spherical halide ions F À , Cl À , Br À , and I À , the linear anion CN À and the bulky anions CH 3 COO À and H 2 PO 4 À .…”
Section: Photoluminescencementioning
confidence: 99%
“…While the miniature nature of the system was intriguing, such a device was going to be difficult for supramolecular chemists to adopt. More user-friendly variants for spatially arraying receptors for solution analysis were thus created by others, such as Pavel Anzenbacher’s sol–gel approach [ 95 96 ]. Yet, the absolute easiest way to array receptors is to use commercially available plates, such as plastic 96-well plates, because the receptors can be dissolved and then dispensed by common 8- and 12-channel pipettes.…”
Section: Reviewmentioning
confidence: 99%
“…However, only few examples of multisensory fluorescent systems for analysis of anions are reported (Anzenbacher et al, 2013 ; Lin et al, 2015 ; Pushina and Anzenbacher, 2017 ). Thus, for instance a fluorescent sensor array based on supramolecular metallogels for the identification of CN − , SCN − , S 2− and I − anions in water was reported by Lin et al ( 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The aqueous solutions of 11 different analytes were correctly identified with LDA analysis. Anzenbacher et al have also reported an anion-sensitive array based on a ratiometric calix[4]pyrrole introduced in poly(ether-urethane) hydrogel matrices with varying comonomer proportions (Anzenbacher et al, 2013 ). This array was used to discriminate eight different anions (acetate, benzoate, fluoride, chloride, phosphate, pyrophosphate, hydrogen sulfide, and cyanide) in urine samples and anti-inflammatory drugs with 100% classification accuracy.…”
Section: Introductionmentioning
confidence: 99%